Analysis of γ Doradus and δ Scuti stars observed by Kepler. Issue Volume 9:Issue S301(2013) (18th February 2014) - Bradley, Paul A.; Guzik, Joyce A.; Miles, Lillian F.; Jackiewicz, Jason; Uytterhoeven, Katrien; Kinemuchi, Karen
Abstract: The Kepler spacecraft observed over 2000 faint stars that were part of our Guest Observer proposals. The stars were selected from the Kepler Input Catalog (KIC) to be in or near the γ Doradus or δ Scuti instability strips (8300 K > T eff > 6200 K and 3.6 < log g < 4.7). The Kepler magnitude was <16 and the contamination factor was < 10 −2 . The goal was to extend the search for "hybrid" δ Sct-γ Dor pulsators to fainter magnitudes. By inspecting the light curves and Fourier transforms, we find 42 δ Sct candidate stars, 299 γ Dor candidates, and 36 "hybrid" candidate stars showing both types of variations.